Inovasi Layanan Perpustakaan Nasional RI Dalam Masa Pandemi Covid-19 - Yuli Maryani; Septa Agustina (Jurnal IPI (Ikatan Pustakawan Indonesia), 2021)
The Covid 19 pandemic has had a changing impact on public service institutions. So that many government agencies or institutions, include National Library of Indonesia, make various innovation to services for the community in Covid-19 pandemic. The purpose of this article is to determine innovations in the library service of the National Library of Indonesia during the Covid 19 pandemic. This article method uses descriptive-qualitative in the form of words / narratives. The data collection techniques used were participant observation through observation, open interviews and documentation of literature studies. During the Covid 19 pandemic, National Library of Indonesia did not lose their minds to provide information services to users, namely by making various innovations in the service sector. The innovations that have been made by the librarian of the National Library of Indonesia are virtual membership cards, direct interaction through live chat and online user guidance from various provinces. Being in a pandemic period builds creative power and has a positive impact on both librarians and visitors.